Nippostrongylus smalesae sp. nov. (Nematoda: Heligmonellidae) collected from Maxomys whiteheadi (Rodentia: Muridae) of Sumatra, Indoneisa - Hasegawa, Hideo; Dewi, Kartika; Fitriana, Yuli S.; Asakawa, Mitsuhiko (Zootaxa, 2017)
Nippostrongylus smalesae sp. nov. (Nematoda: Heligmonellidae) is described from a murid Maxomys whiteheadi collected in Riau, Sumatra, Indonesia. It is readily distinguished from all of the known congeners by having the ray 3 widely diverged distally from the ray 4 in the left lobe of bursa copulatrix. This is the tenth named species of Nippostrongylus. The same species but with slight morphological difference was also found from M. whiteheadi and Niviventer cremoriventer in Kalimantan (Borneo Island), suggesting wide geographical distribution on the Sundashelf islands.